TH3.2: Youth transitions and livestock in Kenya - Bullock, Renee; Miriti, Philip; López, Diana E. (International Livestock Research Institute, 2022)
Globally, youth transitions to adulthood are becoming more complex. The relative importance of key milestones that are used to describe the transition from youth to adulthood are culturally embedded and change across generations. So called ‘critical moments' may include completing education, moving from school to the labour force, leaving home, marriage, and parenthood. In the global south, sub–Saharan Africa in particular, agricultural and livestock assets are also culturally valued and often critical to supporting major achievements in transitions. What can we learn from youth studies to better understand youth engagement in agriculture and livestock sectors? This work aims to bridge youth and gender studies to explore young women's and men's transitions and the various ways that livestock feature in the achievement of key milestones. What are young women's and men's values and experiences as they enter adulthood? How does livestock feature in youth transitions and for whom? Recognizing that gender and age intersect to create and constrain youth opportunities and experiences, we undertake a gendered analysis of livestock value chain actors to explore their perspectives on the importance and attainment of milestones. We use a mixed-methods approach that includes 700 market surveys, 38 focus group discussions, and 20 key informant interviews in 6 counties in Kenya that include pastoral, agro-pastoral, and mixed crop systems in both peri-urban and rural settings. We describe the shifts in cultural values across diverse contexts over time and the various roles that livestock play in supporting youth transitions.